Homeless in Dhaka: Violence, Sexual Harassment, and Drug-abuse (Journal of Health, Population and Nutrition, 2009)
Bangladesh has experienced one of the highest urban population growth rates (around 7% per year) over the past three decades. Dhaka, the capital city, attracts approximately 320,000 migrants from rural areas every year. The city is unable to provide shelter, food, education, healthcare, and employment for its rapidly- expanding population. An estimated 3.4 million people live in the overcrowded slums of Dhaka, and many more live in public spaces lacking the most basic shelter. While a small but growing body of research describes the lives of people who live in urban informal settlements or slums, very little research describes the population with no housing at all. Anecdotally, the homeless population in Dhaka is known to face extortion, erratic unemployment, exposure to violence, and sexual harassment and to engage in high-risk behaviours. However, this has not been systematically documented. This cross-sectional, descriptive study was conducted to better understand the challenges in the lives of the homeless population in 11 areas of Dhaka during a 13-month period from June 2007 to June 2008. A modified cluster-sampling method was used for selecting 32 clusters of 14 female and male respondents, for a sample of 896. In addition to sociodemographic details, this paper focuses specifically on violence, drug-abuse, and sexual harassment. The findings showed that physical assaults among the homeless, particularly among women, were a regular phenomenon. Eighty-three percent of female respondents (n=372) were assaulted by their husbands, station masters, and male police officers. They were subjected to lewd gestures, unwelcome advances, and rape. Male respondents reported being physically assaulted while trying to collect food, fighting over space, or while stealing, by police officers, miscreants, or other homeless people. Sixty-nine percent of the male respondents (n=309) used locally-available drugs, such as marijuana and heroin, and two-thirds of injecting drug-users shared needles. The study determined that the homeless are not highly mobile but tend to congregate in clusters night after night. Income-generating activities, targeted education, gender-friendly community police programmes, shelters and crises centres, and greater community involvement are suggested as policy and programmatic interventions to raise the quality of life of this population. In addition, there is a need to reduce high rates of urban migration, a priority for Bangladesh. Key words: Cross-sectional studies; Descriptive studies; Developing country; Homelessness; Sexual harassment; Substance-abuse; Violence; Bangladesh   doi: 10.3329/jhpn.v27i4.3389 J Health Popul Nutr 2009 Aug;27(4):452-461